Implementation Of Artificial Intelligence In Entrepreneurship: An Empirical Study (Journal of Pharmaceutical Negative Results, 2023)
In recent years, India's entrepreneurship scene has grown. From entrepreneur's perspective this study examines the effectiveness of entrepreneurship using standard decision-making processes and AI. The study used a sample of 50 responses all over India. Entrepreneurs were asked to complete structured questionnaires and personal interviews to assess their opinions on traditional vs artificial intelligence, as well as the relationship between the two and their impact on entrepreneurial decisions. The results revealed that men and women entrepreneurs perceive personality and compatibility tests differently.